Law Enforcement in Resolving Trade Business Conflicts - Hapriyanto, Aditya Restu; Dewi, Putri Maha (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Law has a role in protecting the rights and interests of all parties involved in business, such as consumers and shareholders, as well as workers. The application of law in resolving business disputes allows parties who feel disadvantaged to obtain justice through a transparent and fair legal process. However, in practice, resolving business disputes is often complicated and expensive. Many companies choose to use arbitration or mediation as an alternative to traditional courts in resolving disputes. This research aims to determine the effectiveness of law enforcement in resolving trade business conflicts. The research used is an empirical legal research method using descriptive qualitative research. The results of this research show that commercial law plays an important role because it includes the rules and principles that govern business relationships, contracts, obligations, and the rights of the parties involved. In addition, parties involved in business disputes need to understand the negotiation, arbitration, and court processes and have a strong knowledge of commercial law so that business disputes can be resolved fairly and efficiently, which in turn will support healthy business growth and continuity.